Changes in interferon-gamma and neopterin in female dogs undergoing ovariohysterectomy as elective spay or as treatment of pyometra - Dąbrowski, Roman (Can J Vet Res, 2020)
The objective of this study was to determine serum concentrations of interferon-gamma (INF-γ) and neopterin (Np) in dogs with pyometra admitted for surgical treatment and to compare these concentrations to healthy dogs admitted for elective spay. The effects of the surgical procedure were also evaluated by measuring these markers in both groups of dogs before and after ovariohysterectomy. Our study indicates that pre-surgery concentrations of INF-γ (57.4 ± 26.0 pg/mL) and Np (5.6 ± 0.8 nmol/L) in healthy dogs were significantly lower compared to dogs with pyometra (124.3 ± 87.6 pg/mL for INF-γ; 7.0 ± 1.5 nmol/L for Np) (P < 0.05 in both cases). Furthermore, Np was lower in dogs with pyometra 3 days after surgery compared to healthy controls (P < 0.001). During the post-operative period, INF-γ showed no statistically significant changes in any of the groups, while Np showed lower serum concentration on day 3 than on day 0 in the pyometra group (P < 0.001). No statistically significant correlation was detected between serum concentrations of INF-γ and Np. These results indicate that pyometra causes alterations in serum concentrations of INF-γ and Np in female dogs compared to physiological levels before surgery and during the postoperative period.